ANXIETY DISORDER PERSPEKTIF TAFSIR AL-SYA‘RAWI - Mursyid, Ali; Jannah Ismawati, Miftahul (Asosiasi Dosen PTKIS Indonesia, 2025)
This research is significant for several reasons: First the number of anxiety disorder sufferers has been increasing year by year. Second The numerous challenges of modern life contribute to the prevalence of anxiety disorders. Few scholars have explored anxiety disorders from the perspective of Quranic exegesis, especially in the Tafsir al-Sya‘rawi by Sheikh Muhammad Mutawallī al-Sya‘rawi. While many studies have addressed anxiety disorder from medical and Zen perspectives, few have examined it through the lens of Quranic exegesis and Sufism. Therefore, this study seeks to analyze anxiety disorder from the perspective of Quranic exegesis. The focus of the research is on Muhammad Mutawallī al-Sya‘rawi’s interpretation of anxiety disorder and its relevance. This study is a qualitative research that adopts the approach of Sufi psychotherapy. The data sources used in this research include Tafsir al-Sya‘rawi and other related literature. The method applied involves content analysis by identifying the main themes that emerge in the interpretation regarding mental health anxiety. The research findings indicate that: first, al-Sya‘rawi’s interpretation of verses related to anxiety disorder suggests that excessive anxiety can be addressed or reduced through the enhancement of faith, particularly through tawakkal (trust in God), ikhlas (sincerity), sabar (patience), rida (contentment), and dzikir (remembrance of God). Second, the relevance of this interpretation in the context of modern society is highly significant. This is evidenced by previous studies, such as those demonstrating that tawakkal can help reduce anxiety related to hemodialysis therapy in patients with chronic kidney failure, ikhlas can provide peace and meaning in life, reducing anxiety caused by situational changes during the Covid-19 pandemic, and dzikir can serve as a psychological therapy for the elderly, helping to alleviate anxiety and improve mental well-being by offering tranquility and hope